The Solar System in 3-D - Schenk, Paul M.; Gwynn, David W.; Tutor, James (Lunar and Planetary Institute, 2005)
LPI slide set converted to a PowerPoint set by the staff of the Spacecraft Planetary Imaging Facility, Cornell University A study of geology, atmospheres, and other structures using stereo imagery of the planets, their satellites, and the Sun. compiled by Paul M. Schenk, David Gwynn, and James Tutor. The Solar Corona in X-Rays--Discovery Rupes, Discovery Region, Mercury--Kaikilani (Complex Crater), Nsomeka Planitia, Venus--Carmenta Farra (Pancake Domes), Eistla Regio, Venus--Calderas and Tessera, Ovda Regio, Venus--Corona, Ovda Regio, Venus--Ridge Belt, Ishtar Terra, Venus--Mount St. Helens, Washington, USA, Earth--Eruption of Klyuchevskaya, Kamchatka, Russia, Earth--Kurile-Kamchatka Trench, Northwestern Pacific Basin, Earth--Owens Valley, California and Nevada, USA, Earth--Grand Canyon, Arizona, USA, Earth--Thunderstorms, Brazil, Earth--Eye, Typhoon Emilia, Western Pacific, Earth--Montes Haemus, Mare Serenitatis, Moon--King (Complex Crater), Farside Terra, Moon--Catena Davy (Imbrium Basin Ejecta), Mare Nubium, Moon--Apollo 17 Landing Site, Taurus-Littrow Valley, Moon--Surface of the Moon, Boulders, Taurus-Littrow Valley, Moon--Surface of the Moon, Astronaut, Oceanus Procellarum, Moon--Surface of the Moon, Rover, Hadley Rille, Moon--Surface of the Moon, Soil Close-Up, Fra Mauro Highlands, Moon--Apollinaris Patera, Elysium Planitia, Mars--Eastern Tithonium Chasma, Valles Marineris, Mars--Ma'adim Vallis, Terra Cimmeria, Mars--Valley Networks in Libya Montes, Tyrrhena Terra, Mars--Rabe (Terrain Softening), Noachis Terra, Mars--Surface of Mars ("Twin Peaks"), Ares Vallis, Mars--Surface of Mars ("Sojourner"), Ares Vallis, Mars--Grooves and Craters, Phobos, Mars--Gaspra, Asteroid Belt--Haemus Montes, Io, Jupiter--Isis (Central Pit Crater), Ganymede, Jupiter--Galileo Regio, Ganymede, Jupiter--Saturn--Ormazd Region, Rhea, Saturn--Coronae, Miranda, Uranus--Sylph Chasma Region, Ariel, Uranus--Pluto and Charon--Overview, Solar System.